(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Repeated endoscopy is required to detect & follow up of esophageal varices (OV) in cirrhotic patients. Objective: For discomfort and unwillingness lo do the endoscopy directed us to evaluate liver stiffness measurement (LSM) for lhe prediclion ofO V. Methods: A cross sectional observational study was conducted between July 2010 to July 2011. A total of 50 patients with cirrhosis were divided into three groups. Group-I patients had no varix (n=4), group-II had Grade-I OV (n=23) and group-UI had Grade-II/III OV (n=23 ) at endoscopy. Liver stiffness was measured by fibroscan & data was analyzed by SPSS. Results: Mean age were 35.20 ± 11.36 years with highest frequency 19 (38 %) in 21-30 years age group. Etiologies were different with leading causes includes HBV (76%) followed by HCV (6%), alcohol (2%) and 14% were unknown. Liver stiffness did not significantly differ from group-I & group-II, but was significantly higher in group III than group-II & group I. Liver stiffness was nol accurate in the prediction of grade-I oesophageal variees [Arca under the curve (AUC)] = 23.6%. Liver stiffness at a cut off value 32.52 kPa with sensitivity, specificity, positive predictive value, negative predictive value, accuracy respectively 82.6%, 77.8 %, 76 %, 84%, 80% can predict the Grade-II-Ill oesophageal varices (AUROC = 85.2%). Conclusion: Liver stiffness may be suitable for prediction of Grade-II-III oesophageal varices, not for the screening of the presence of oesophageal varices.